2023
DOI: 10.2147/jhc.s410891
|View full text |Cite
|
Sign up to set email alerts
|

LINC00886 Facilitates Hepatocellular Carcinoma Tumorigenesis by Sequestering microRNA-409-3p and microRNA-214-5p

Abstract: Purpose As the major subtype of liver cancer, hepatocellular carcinoma (HCC) suffers from high mortality and is prone to recurrence. Long non-coding RNAs (lncRNAs) are well characterized to be pivotal players contributing to HCC pathogenesis and progression. Therefore, this study intended to probe the biological functions of LINC00886 in hepatocarcinogenesis. Patients and Methods Quantitative real-time polymerase chain reaction (qRT-PCR) was applied to analysis of LINC0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…MiR-409-3p not only exists in tissues and cells but also stably exists in circulating body fluids. For the most part, miR-409-3p acts as a tumor suppressor and was reported to be downregulated in a minimum of 13 cancers, including NSCLC ( 12 , 14 - 17 , 19 - 21 ), BC ( 24 , 26 , 27 , 29 , 30 ), CC ( 31 - 35 ), osteosarcoma ( 36 - 39 ), GC ( 40 - 44 ), CRC ( 45 , 46 , 48 - 51 ), OC ( 53 - 55 ), ccRCC ( 57 , 58 ), BCa ( 59 , 61 ), PTC ( 62 ), AML ( 65 , 66 ), oligodendrogliomas ( 67 ), melanoma ( 68 ), TSCC ( 70 ), glioma ( 79 ), fibrosarcoma ( 81 ) and HCC ( 83 , 84 ). However, miR-409-3p also serves as an oncogene to promote tumor progression.…”
Section: Aberrant Expression Of Mir-409-3p In Cancersmentioning
confidence: 99%
See 3 more Smart Citations
“…MiR-409-3p not only exists in tissues and cells but also stably exists in circulating body fluids. For the most part, miR-409-3p acts as a tumor suppressor and was reported to be downregulated in a minimum of 13 cancers, including NSCLC ( 12 , 14 - 17 , 19 - 21 ), BC ( 24 , 26 , 27 , 29 , 30 ), CC ( 31 - 35 ), osteosarcoma ( 36 - 39 ), GC ( 40 - 44 ), CRC ( 45 , 46 , 48 - 51 ), OC ( 53 - 55 ), ccRCC ( 57 , 58 ), BCa ( 59 , 61 ), PTC ( 62 ), AML ( 65 , 66 ), oligodendrogliomas ( 67 ), melanoma ( 68 ), TSCC ( 70 ), glioma ( 79 ), fibrosarcoma ( 81 ) and HCC ( 83 , 84 ). However, miR-409-3p also serves as an oncogene to promote tumor progression.…”
Section: Aberrant Expression Of Mir-409-3p In Cancersmentioning
confidence: 99%
“…In general, miR-409-3p has been strongly connected with cell growth and apoptosis in various cancers. In HCC, Li et al ( 84 ) found that silencing LINC00886 upregulated the expression of miR-409-3p, weakened the proliferation of HCC cells (Hep3B, Huh7) and promoted apoptosis. Conversely, it promoted the proliferation of Hep3B as well as Huh7 proliferation and inhibited apoptosis.…”
Section: Biological Roles Of Mir-409-3p In Cancers In Vitromentioning
confidence: 99%
See 2 more Smart Citations